Biopesticide of the Mixture of Crescentia Cujete and Calotropis Gigantea to Control Spodoptera Frugiperda J.E Smith (Lepidoptera: Noctuidae) - Sulastri, Elsa; Kasim, Niken Nur; Arifin, Asia; Sjam, Sylvia (Journal of Agriculture, 2025)
Biopesticides offer an environmentally friendly alternative for pest management. In Indonesia, Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae), or fall armyworm, is a major pest affecting maize by damaging the apical meristem and upper leaves. This study evaluated a biopesticide formulated from a mixture of Crescentia cujete fruit and Calotropis gigantea leaf extracts on the population and damage severity of S. frugiperda. A completely randomized design with three treatments (P1: 5%, P2: 2.5%, and P3: 0%/control) and three replicates was used. Additionally, a farmer's practice using synthetic pesticides was included for comparison. Applications were carried out weekly, and observations were conducted on pest population and leaf damage severity, assessed using a 1–9 Davis scale. ANOVA followed by LSD (5%) and regression analysis were used for statistical evaluation. The results showed that the 5% extract (P1) significantly reduced both pest population and damage severity compared to the control and farmer treatment. The severity in P1 and P2 was 25.22% and 27.06%, respectively, while P3 and the farmer's treatment showed 43.02% and 47.25%. Regression analysis revealed a strong positive correlation (R² = 0.987) between the S. frugiperda population and severity, indicating that a 1% increase in population corresponds to a 4.74% rise in severity. These findings demonstrate that the extract mixture is an effective and eco-friendly biopesticide. It offers a sustainable alternative for fall armyworm management, potentially reducing dependence on chemical pesticides while minimizing environmental impact.